Changing Conditions for Local Food Actors to Operate Towards Agroecology During the COVID-19 Pandemic - Frank, Markus (2022)
Given the novel character of disturbances caused by the pandemic in food systems, initial studies have been conducted to stress the reinforced urgent need for food systems’ transformation toward sustainability. First assessments, conducted in the early months of the pandemic, found that local food actors responded to changing production and marketing conditions by implementing alternative practices under the umbrella of agroecology. However, given the unprecedented and dynamic character of the pandemic in regional situations, and related context-specific changes caused in food system actors’ operations, case studies are needed to assess in more detail under which changing conditions food actors implemented alternative practices. Moreover, the maintenance of practices as conditions normalize, and food actors’ transformative potential in relation to the principles of agroecology, need further assessment. In response to these emerging issues, we provide insights into our case study research conducted during 2021 in a local food system in Argentina. The aim of this research was to study how changing conditions triggered local food actors to (re-)frame their objectives and activities regarding marketing, and to assess the relevance of agroecological principles as a means of responding to changing conditions and to unfold longer-term transitions. We identified local producer shops (n = 5) and markets (n = 4) that were established or consolidated by self-organized producer groups (SOPGs) during the first months of the pandemic. Using semi-structured interviews with SOPG members (n = 12) and qualitative content analysis, we found that alternative practices were adopted in response to different changing conditions, and new needs and opportunities for producers and consumers brought about by the pandemic. Objectives pursued, and activities undertaken by the groups revealed reactive short-term mitigation strategies, and proactive longer-term transformative objectives. The relational analysis between practices and agroecological principles showed that the principles became important Frank et al. Local Food Actors During COVID-19 means of responding to changing conditions and to unfold longer-term transitions. The cases illustrate how local food actors operationalized agroecological principles, and in turn how principles can be used to investigate the nature and potentials of food actors’ alternative practices, highlighting the relevance of agroecology to co-design sustainability transitions in local food systems and to mitigate possible future crisis. Dado el carácter novedoso de las perturbaciones provocadas por la pandemia en los sistemas alimentarios, se han realizado estudios iniciales para enfatizar la necesidad urgente reforzada de alimentos transformación de los sistemas hacia la sostenibilidad. Primeras evaluaciones, realizadas en los primeros meses de la pandemia, encontró que los actores alimentarios locales respondieron a cambios condiciones de producción y comercialización mediante la implementación de prácticas alternativas bajo paraguas de la agroecología. Sin embargo, dado el carácter dinámico y sin precedentes de la pandemia en situaciones regionales, y los cambios específicos relacionados con el contexto causados ​​en los alimentos operaciones de los actores del sistema, se necesitan estudios de caso para evaluar con más detalle bajo en qué condiciones cambiantes los actores alimentarios implementaron prácticas alternativas. Es más, el mantenimiento de las prácticas a medida que las condiciones se normalizan, y la transformación de los actores alimentarios potencial en relación con los principios de la agroecología, necesita una evaluación adicional. En respuesta a estos problemas emergentes, brindamos información sobre nuestra investigación de estudio de caso realizada durante 2021 en un sistema alimentario local en Argentina. El objetivo de esta investigación fue estudiar cómo las condiciones cambiantes impulsaron a los actores alimentarios locales a (re)enmarcar sus objetivos y actividades relacionadas con la comercialización, y para evaluar la pertinencia de los principios agroecológicos como un medio para responder a las condiciones cambiantes y desarrollar transiciones a más largo plazo. Identificamos tiendas de productores locales (n = 5) y mercados (n = 4) que se establecieron o consolidados por grupos de productores autoorganizados (SOPG) durante los primeros meses de la pandemia. Uso de entrevistas semiestructuradas con miembros de SOPG (n = 12) y análisis de contenido cualitativo, encontramos que se adoptaron prácticas alternativas en respuesta a diferentes condiciones cambiantes, y nuevas necesidades y oportunidades para productores y consumidores provocados por la pandemia. Objetivos perseguidos, y actividades emprendidas por los grupos revelaron estrategias reactivas de mitigación a corto plazo, y objetivos transformadores proactivos a más largo plazo. El análisis relacional entre prácticas y principios agroecológicos mostraron que los principios se volvieron importantes franco et al. Actores alimentarios locales durante el COVID-19 medios para responder a las condiciones cambiantes y desarrollar transiciones a más largo plazo. Él Los casos ilustran cómo los actores alimentarios locales pusieron en práctica los principios agroecológicos y, en cómo se pueden utilizar los principios para investigar la naturaleza y el potencial de los actores alimentarios prácticas alternativas, destacando la relevancia de la agroecología para co-diseñar la sostenibilidad transiciones en los sistemas alimentarios locales y mitigar posibles crisis futuras.